2019
DOI: 10.1051/matecconf/201926601011
|View full text |Cite
|
Sign up to set email alerts
|

Review on Project Manager’s Leadership Skills in the Pre-Construction Phase of Sustainable Construction Projects

Abstract: Project managers have played a vital role in sustainable construction projects by integrating the concept of sustainability into their practices. The role of project manager is important in all phases of sustainable construction projects but especially in the pre-construction phase when the greatest challenges that require their involvement occur. This requires project managers to have effective leadership skills to think a project through and remain focused on the end goal. Thus, the aim of this paper is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In addition, the appointment of the project manager will influence the success or failure of the project. Therefore, a successful project consultant should perform several roles and responsibilities at the same time, and play a vital role in all stages of the construction project (the initial stage, design stage, construction stage, pre-construction stage, and post-construction stage) [24].…”
Section: Role and Responsibilities Of The Project Consultants In The mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the appointment of the project manager will influence the success or failure of the project. Therefore, a successful project consultant should perform several roles and responsibilities at the same time, and play a vital role in all stages of the construction project (the initial stage, design stage, construction stage, pre-construction stage, and post-construction stage) [24].…”
Section: Role and Responsibilities Of The Project Consultants In The mentioning
confidence: 99%
“…Industry The construction industry needs mainly leadership because the success or failure of construction projects largely depends on who leads and coordinates them [24]. However, 80% of project failures are caused by poor leadership, including insufficient leadership, lack of teamwork, low efficiency of problem-solving and weak communication skills [36].…”
Section: Leadership Skills Of the Project Consultants In The Construcmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant literature advocates the importance of the project manager and his strong role in leading the project to success. Further, Zulkiffli and Lattifi (2019) indicated that project managers played a vital role in sustainable building projects by integrating sustainability into their practices. In all phases of sustainable construction projects, the role of project manager is important, but especially in the pre-construction phase when the greatest challenges that require their involvement are present.…”
Section: Project Manager's Skillsmentioning
confidence: 99%
“…In addition, empowering the project team will inspire them as well as improving efficiency and productivity. Besides, empowering not only motivates the project manager, but also establishes trust and delegates the project team throughout the right direction (Zulkiffli & Latiffi, 2019).…”
Section: Muda Et Al (2017)mentioning
confidence: 99%